2017
DOI: 10.1038/s41598-017-03323-6
|View full text |Cite
|
Sign up to set email alerts
|

Conformational plasticity and evolutionary analysis of the myotilin tandem Ig domains

Abstract: Myotilin is a component of the sarcomere where it plays an important role in organisation and maintenance of Z-disk integrity. This involves direct binding to F-actin and filamin C, a function mediated by its Ig domain pair. While the structures of these two individual domains are known, information about their relative orientation and flexibility remains limited. We set on to characterise the Ig domain pair of myotilin with emphasis on its molecular structure, dynamics and phylogeny. First, sequence conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…Overall, the EOM-selected models tended to be more compact than those in the random pool. This is visible from the shift to lower values of D max and R g derived from the selected models compared to the distribution derived from the original pool, as the most extended models were not selected (Fig 1E,S1C and S1D Fig) . Based on this analysis, Trx-MYOT displays a tendency to occupy more compact conformations compared to a chain with random coil linkers, in line with the predicted compactness (Fig 1B ) and the disorder tendency analysis [23].…”
Section: Myotilin Is a Conformational Ensemble In Solutionsupporting
confidence: 79%
See 2 more Smart Citations
“…Overall, the EOM-selected models tended to be more compact than those in the random pool. This is visible from the shift to lower values of D max and R g derived from the selected models compared to the distribution derived from the original pool, as the most extended models were not selected (Fig 1E,S1C and S1D Fig) . Based on this analysis, Trx-MYOT displays a tendency to occupy more compact conformations compared to a chain with random coil linkers, in line with the predicted compactness (Fig 1B ) and the disorder tendency analysis [23].…”
Section: Myotilin Is a Conformational Ensemble In Solutionsupporting
confidence: 79%
“…The previously performed disorder tendency analysis of full-length myotilin revealed that the N-terminal region of myotilin displays characteristics of an intrinsically disordered protein (IDP) [23]. The meta-structure analysis, which reflects how likely a specific residue is to be located within a compact 3D structure, was carried out as described previously [6], and indicated a tendency for local compactions in the N-terminal ID region (Fig 1B).…”
Section: Myotilin Is a Conformational Ensemble In Solutionmentioning
confidence: 72%
See 1 more Smart Citation
“…Almost all MYOT variants have been located in exon 2 in the amino-terminal region, an intrinsically unstructured region [ 135 ]. Two separate studies described MYOT missense variants affecting the same residue (p.Arg6Gly and p.Arg6His), both causing severe forms of skeletal myopathy, suggesting this residue is a mutational hotspot [ 136 , 137 ].…”
Section: Z-disc Proteins In Myopathy and Cardiomyopathymentioning
confidence: 99%
“…This mechanism is not restricted only to collagens but was also observed for pancreatic cancer cells growing on the surface composed of fibronectin and laminin, where cancer cells became resistant to DOX, CIS and 5-fluorouracil (5-FU) 44 and for breast cancer cell line MDA-MB-231 growing on the surface of fibronectin and type I collagen that became resistant to PAC 45 . MYOT is a structural protein that interacts with many other proteins in cells 46 . IgG-like domains of MYOT are responsible for dimerization and binding of other proteins like F- and G-actin 31 , 47 or filamin C 32 .…”
Section: Discussionmentioning
confidence: 99%